Plan de negocio para la creación de microempresa de diseño y mantenimientos de jardinería a domicilio en la zona residencial del cantón Samborondón - Salazar Bravo, María Edilma (2019)
Life Garden is a company located in the province of Durán Canton of Guayas, created to meet the needs of the residents of the canton Samborondón that have green areas in their residence. Through the research conducted it was identified that the urban area of the Samborondón Canton is in full development, ideal for projects and ventures focused on the real estate area due to the development of new residential complexes, where one of its main focuses is landscaping……….